Comparison of different locking plate fixation methods in lateral malleolus fractures. Issue 3 (June 2019) - Bilgetekin, Yenel Gürkan; Çatma, Mehmet Faruk; Öztürk, Alper; Ünlü, Serhan; Ersan, Önder
Highlights: One-third tubular and anatomic locking plates have similar clinical and radiological outcomes for treatment of lateral malleolar fractures. Distal anatomic locking plates allows more distal screws which can be considered when treating more distal fractures. One-third tubular locking plates reduce treatment cost so anatomical plates can be reserved for exact indications. Abstract: Background: Several fixation methods may be used for displaced lateral malleolar fractures. We aimed to compare clinical and radiologic outcomes associated with use of locking one third tubular plate vs. anatomical distal fibula locking plate in lateral malleolar fractures. Methods: A total of 62 orthopedic patients operated for lateral malleolus fracture were included in this retrospective study. Patients were divided into two groups regarding the plate used for fixation as locking one third tubular plate (group I; n = 37) and locking anatomical distal fibula plate (group II; n = 25). Data on Danis–Weber ankle fracture classification (Type A, Type B), duration of follow up, clinical outcome [ankle range of motion (ROM), American Orthopaedic Foot & Ankle Society (AOFAS) score], radiological outcomes (adequacy of reduction, loss of alignment), time to fracture healing and complications were recorded in study groups. Results: No significant difference was noted between groups in terms of AOFAS score [87.0 (73–100) vs. 85.0 (71–100), respectively (p = 0.339)] and no patients had severe restriction in sagittal and hindfoot motion in both groups. The two groups showed similar healing time [9.0 (7–13) weeks vs. 10.0 (8–13) weeks, respectively (p = 0.355)] and complication rate [0.0% vs. 4.0%, respectively (p = 0.403)]. Conclusions: This study revealed no significant difference between use of locking one third tubular plate and locking anatomical distal fibula plate in lateral malleolar fixation, in terms of clinical and radiological outcomes, complication rates and fracture healing time.